Effects of cinnamon essential oil on the physiological metabolism of Salmonella enteritidis - Zhang, Zhen; Zhao, Yuanyuan; Chen, Xueqin; Li, Wei; Wang, Li; Li, Wen; Du, Jianming; Zhang, Shengxiang (Frontiers in Microbiology, 2022)
Food safety and health were the themes of today's society. As a class of food-borne pathogens, Salmonella enteritidis had become one of the common zoonotic pathogens. Because chemical preservatives had certain harmfulness and had been questioned, it was particularly important to find green and safe natural preservatives. The advantages of plant essential oils (EOs) were that they were green and safe, had a wide range of antibacterials, and were not easy to form drug resistance. In recent years, studies had found that EOs have excellent antibacterial activity, but their antibacterial mechanism had not been conclusive, which had certain limitations in their application in the food field. Cinnamon essential oil (CEO) extracted from dried cinnamon was a secondary metabolite of cells and a very important natural food flavor. More importantly, it was non-toxic to the human body and had been proven to have good antibacterial effect, but its antibacterial mechanism was still unclear. Therefore, it was of great practical significance to carry out the research on the antibacterial mechanism of CEO on S. enteritidis. In this work, S. enteritidis was used as the test bacteria, and CEO was selected as the antibacterial agent to study the antibacterial mechanism. By studying the physiological metabolism of S. enteritidis cells by CEO the influence of CEO on the bacteriostatic mechanism of S. enteritidis was systematically elucidated. First, it was found by resazurin method that CEO treatment would reduce the activity of bacterial metabolism; key enzyme activities mainly reflected in the TCA cycle were inhibited, thus affecting the respiration of S. enteritidis; and by inhibiting adenosine triphosphate (ATP) The content and ATP enzyme activity affect the level of energy metabolism in the body; it can also affect the physiological metabolism level of bacteria by inhibiting the metabolism of proteins and other substances. Therefore, this paper was expected to provide a theoretical basis for the development of new natural food preservatives and the prevention and control of S. enteritidis.